Testicular function among testicular cancer survivors treated with cisplatin‐based chemotherapy. (31st December 2015) - Namekawa, Takeshi; Imamoto, Takashi; Kato, Mayuko; Sazuka, Tomokazu; Fuse, Miki; Sakamoto, Shinichi; Kawamura, Koji; Ichikawa, Tomohiko
Abstract: Purpose: The aim of our study was to identify the clinical predictors of spermatogenesis recovery in testicular cancer (TC) patients after chemotherapy and to determine the recuperation period for spermatogenesis. Methods: Patients treated for TC from January 1982 to November 2001 at Chiba University Hospital were retrospectively assessed. Thirty‐five patients who met the following criteria were examined—(i) underwent both high orchiectomy and cisplatin‐based chemotherapy; (ii) had semen analyses and hormonal measurements; and (iii) were alive with no evidence of disease. Clinical variables associated with normalization of spermatogenesis after chemotherapy were examined. Time to recover normospermia was also evaluated using Kaplan–Meier analysis. Results: The observation period was 13.3 ± 5.6 years. Reappearance of sperm was confirmed in 85.7 % of patients, and 54.3 % of patients recovered normospermia. Age at diagnosis <25 years ( p = 0.0057), number of chemotherapy cycles <4 cycles ( p = 0.0042), and follicle‐stimulating hormone at the end of chemotherapy <18 mIU/ml ( p = 0.0220) were independent factors related to post‐chemotherapy normalization of semen findings. The median (95 % CI) time to recover normospermia was 40 (range 22–96) months. Conclusions: These findings help to predict whether spermatogenesis will recover and its timing. They may also help clinicians identify and manage TC patients at a higher risk of prolonged azoospermia after chemotherapy.